How spies think ten lessons in intelligence - Omand, David (Viking, an imprint of Penguin Books, 2020)
From the former director of GCHQ, learn the methodology used by the British intelligence agencies to reach judgements, establish the right level of confidence and act decisively. Intelligence officers discern the truth. They gather information, often contradictory or incomplete, and, with it, they build the most accurate possible image of the world. With the stakes at their absolute highest, they must then decide what to do. In everyday life, you are faced with contradictory, incomplete information, too. Reading the news on social media, figuring out the next step in your career, or trying to discover if gossip about a friend is legitimate, you are building an image of the world and making decisions about it. Looking through the eyes of one of Britain's most senior ex-intelligence officers, Professor Sir David Omand, How Spies Think shows how the big decisions in your life will be easier to make when you apply the same frameworks used by British intelligence. Full of revealing examples from his storied career, including key briefings with Prime Ministers from Thatcher to Blair, and conflicts from the Falklands to Afghanistan, Professor Omand arms us with the tools to sort fact from fiction, and shows us how to use real intelligence every day.